PERJUANGAN TOKOH PRIBUMI PADA NOVEL “NAMAKU ALAM” KARYA LEILA S. CHUDORI - Rahmalia, Nadia Andi; Zahra Salwa, Reva; Yuza, Niken Sabika; Fadhilla, Indah (Universitas Hamzanwadi, 2025)
This study aims to describe the historical reality and social stratification in the novel My Name is Nature by Leila S. Chudori using the theory of materialism and the theory of social class developed by Karl Marx. The type of research used is qualitative descriptive research, where data is collected through reading, recording, and literature study methods. The data analysis process is carried out using a descriptive approach. The results of this study show a picture of the historical reality that occurred in 1965, as well as social conflicts that are manifested in the division of social classes which are divided into four categories. The upper class is depicted through the Sastrowidjojo family who live in Papandayan, Bogor, who have the power to oppress the lower class. The lower class is depicted as a marginalized, poor, and weak society. This study also shows a shift in power from the dominant class to the more advanced class, which creates change or revolution. In addition, ideology is also revealed as a view that tries to describe a certain situation with the aim of deceiving others, when in fact the ideology only benefits the ruling class.